Study on the mass transfer of SO2 in ammonia-based desulfurization process - Yang, Guohua; Wu, Di; Gou, Yuanbo; Dong, Yiyuan; Jiang, Jin; Chen, Yafen; Zhang, Ming; Song, Ci; Jiang, Jiankang; Jia, Yong (Frontiers in Materials, 2022)
The coal hydrogen production process requires high-temperature steam as a reactant. Coal-fired boilers are usually used to provide high-temperature steam. The ammonia-based desulphurization process is an effective technology to remove SO2 in the coal-fired flue gas. However, the mass transfer coefficient of SO2 in such an engineered process is not readily available in the literature. In this paper, experiments were carried out to investigate the mass transfer process of SO2 absorption. Combing calculating the air and liquid contact area of the droplet and liquid membrane on the tower wall, the mass transfer coefficient contain parameters pH, gas flue rate and liquid to gas ratio was proposed. The comparison results show that the calculated SO2 mass transfer rate agrees well with the measured data. The relative error of the calculated and experimental values was less than ±20%. This proposed mass transfer coefficient appears to be beneficial for the design and operation of ammonia-based desulfurization FGD system.